The prognostic significance of tumour–stroma ratio in oestrogen receptor-positive breast cancer - Downey, C L (Nature Publishing Group, 2014)
BACKGROUND: A high percentage of stroma predicts poor survival in triple-negative breast cancers but is diminished in studies of unselected cases. We determined the prognostic significance of tumour–stroma ratio (TSR) in oestrogen receptor (ER)-positive male and female breast carcinomas. METHODS: TSR was measured in haematoxylin and eosin-stained tissue sections (118 female and 62 male). Relationship of TSR (cutoff 49%) to overall survival (OS) and relapse-free survival (RFS) was analysed. RESULTS: Tumours with ⩾49% stroma were associated with better survival in female (OS P=0.008, HR=0.2–0.7; RFS P=0.006, HR=0.1–0.6) and male breast cancer (OS P=0.005, HR=0.05–0.6; RFS P=0.01, HR=0.87–5.6), confirmed in multivariate analysis. CONCLUSIONS: High stromal content was related to better survival in ER-positive breast cancers across both genders, contrasting data in triple-negative breast cancer and highlighting the importance of considering ER status when interpreting the prognostic value of TSR.